Protection of Person’s Dignity from Verbal Abuse in the Old Georgian Law - Chachanidze, Elza (Journal of Law, 2019)
Infringement of person’s dignity can take place via action as well as verbally. Compared to assault and battery, the verbal abuse is a milder form of infringement of person’s dignity. The purpose of this article is to study the legal protection of a person’s dignity, in particular, the issue of responsibility for verbal abuse under the old Georgian law. In this regard, the norms from Georgian Legal Monuments, court practice and historical sources are discussed. Based on the interpretation of legal terms, the signs of components of delict are characterized; the sanctions indicated by the lawmakers are compared with the penalties used in practice. The casuistic nature of old Georgian law is also revealed in relation to the mentioned delict. Taking under consideration these circumstances, other cases of verbal abuse and abuse upon the master by the clergymen, woman and serf is separately distinguished and characterized in the article. Regardless of the circumstances mentioned, general norms of verbal abuse are also in the legal monuments, which indicate that not only the cases of specific verbal abuse, provided for by the norms, were punishable, but the law generally protected the dignity of a person. The social status of both the insulted as well as the insulting person had to be taken into consideration, when imposing a punishment. Proprietary sanctions were mostly applied in relation to these actions, and the compensation was often paid in favour of the insulted person. Despite the above-mentioned, we cannot say unequivocally that verbal abuse was a private delict in old Georgian law, as even in this case the determining factor was to whom the abuse would take place.